Design Recommendations for Humidification-dehumidification Solar Water Desalination Systems. (February 2017) - Shalaby, S.M.; Bek, M.A.; Kabeel, A.E.
Abstract: The productivity of the humidification-dehumidification solar desalination systems (HDHSDS) significantly increases when the temperature of the feed water increases, so, high temperature solar water collectors as parabolic trough or evacuated tube collectors are recommended for these systems. On the other hand, the effect of air temperature on the productivity of the HDHSDS is insignificant. Thus, the utilization of solar air heater is not recommended in these systems. Based on these recommendations, three research points are suggested for future work: 1) using the recovered PV thermal energy for heating the feed water in the HDHSDS. This will provide an annual fresh water productivity more than 833 L/m 2 of PV in addition to 278 kWh of electricity; 2) using phase change material with melting temperature around 90 ˚C as a thermal energy storage medium to provide feed water with high and almost constant temperature during the day and keeps the system in operation 24 h/day; 3) using the thermal energy rejected from the thermal power cycles for water heating in the HDHSDS.